Information technology and risk factors for evaluating the banking industry in the Taiwan: an application of a Value Chain DEA - Wang, Mu-Shun; Lu, Shih-Tong (Journal of Business Economics and Management, 2015)
The main purpose of the paper is utilizing a new tool to measure the marginal benefits of information technology on productivity based upon identifying the two-stage best practice frontier. This study utilizes value-chain data envelopment analysis to investigate the effects of Information Technology and the trading activities of financial derivatives on the technical efficiency of a bank’s production process through a two-stage analytical study with a firm-level data set. We find the impact of indicators related to capital adequacy ratios, exchange rate volatility, interest rate volatility, and long-term loans in relation to capital and ownership structure. Technical efficient precedes a reduction in problem loans, concentration of the operating units and developing information technology and utilization of financial derivatives. This paper provides a theoretical rationale and conceptualizing risk factors with environmental uncertainty. The innovation variables are determinants of the bank efficiency on Basel III Accord.